FORMAL AND INFORMAL COMMUNICATION IN NEW PRODUCT DEVELOPMENT TEAMS: THE MEDIATIONEFFECT OF TEAM TRUST - Polat, Volkan; Lynn, Gary; Akgun, Ali; Emre, Onur (UNIV NOVE JULHO, 2018)
New product development (NPD) projects are costly, and fragile against failures as compared to other structures. This study has a holistic view of team factors to examine their relationship with team communication. Communication contributes to technical and practical processes such as learning, new idea development, and creativity. Trust has become prominent by affecting outcomes and processes indirectly, and changing relationships within team. This paper attempted to offer a contribution to the technology and innovation management (TIM) literature by presenting a model for researchers and project managers to understand potential interrelationships among team level factors (team autonomy, stability, member experience, and empowerment), team trust, and team formal and informal communication in NPD teams.
Keywords: New Product Development; Team Communication; Team Trust; Stability; Autonomy; INTEGRATIVE MODEL; VIRTUAL TEAMS; WORK TEAMS; CONSEQUENCES; ANTECEDENTS; TECHNOLOGY; MANAGEMENT; CONFLICT; BARON; Business & Economics